Red dots caught red handed: Dermoscopy of genital psoriasis - Balachandra Suryakant Ankad; Mahajabeen Madarkar (Wolters Kluwer Medknow Publications, 2017)
Dermoscopy is an in vivo diagnostic technique that aids in the visualization of epidermis, dermoepidermal junction, and papillary dermis. Histopathology contributes tremendously in confirming the clinical diagnosis of unusual presentations of inflammatory skin disorders. Being noninvasive, dermoscopy assists significantly in differentiation of many inflammatory skin disorders which clinically resemble one another. In this report, authors describe the importance of dermoscopy in the diagnosis of genital psoriasis which was mimicking dermatophytic infection and contact dermatitis.